Innate immune response to human bone marrow fibroblastic cell implantation in CB17 scid/beige mice. - Xia, Z; Taylor, P; Locklin, R; Gordon, S; Cui, Z; Triffitt, J (2006)
Immunocompromised mouse models have been extensively used to assess human cell implantation for evaluation of cytotherapy, gene therapy and tissue engineering strategies, as these mice are deficient in T and B lymphoid cells. However, the innate immune response and its effect on human cell xenotransplantation in these mouse models are mainly unknown. The aim of this study is to characterise the myeloid populations in the spleen and blood of CB17 scid beige (CB17 sb) mice, and to study the inflammatory cell responses to xenogeneic implantation of enhanced green fluorescent protein (GFP)-labelled human bone marrow fibroblastic (HBMF) cells into CB17 sb mice. The results indicate that even though CB17 sb mice are deficient in B- and T-cells, they exhibit some increases in their monocyte (Mo), macrophage (Mphi) and neutrophil (Neu) populations. NK cell and eosinophil populations show no differences compared with wild-type Balb/C mice. An innate immune response, identified by CR3 (CD11b/CD18)-positive myeloid inflammatory cells and F4/80-positive macrophages, was evident in the tissues where HBMF cells were implanted. As a consequence, the majority of implanted HBMF cells were eliminated by 4 weeks after implantation. Interestingly, the mineralised matrix formed by osteogenic HBMF cells was also eroded by multinuclear Mphi-like giant cells. We conclude that CB17 sb mice retain active innate immune cells, which respond to HBMF cell xenotransplantation. This study highlights the importance of the innate immune cells in the anti-xenograft response and suggests that strategies to block the activities of these cells may ameliorate the progressive long-term elimination of xenotransplants.